Evaluation of the Impact of Crude Oil Contamination on Soil's Physicochemical Characteristics, Micro-flora and Crop Yield - Okafor, Ugochukwu Chukwuma (Tropical Aquatic and Soil Pollution, 2023)
The effects of crude oil pollution on soil physicochemical properties, microflora, and ecotoxicity were evaluated. Soil samples were contaminated with crude oil, and the effects of contamination on the physicochemical parameters, microflora, and growth index of bean (Phaseolus vulgaris) seeds were studied over a 6-month period. The heterotrophic bacteria isolated from the uncontaminated soil were Micrococcus, Klebsiella, Flavobacterium, Bacillus, Pseudomonas, and Serratia species, and the moulds included microbes such as Aspergillus niger, Fusarium, and Mucor sp. Petroleum contamination increased the pH of the soils to alkaline values while increasing the total nitrogen, organic carbon, and phosphorus contents. Electrical conductivity, nitrogen content, and phosphorus content were significantly reduced after petroleum contamination (p ˂ 0.05). The heavy metal contents of the contaminated soils decreased with increasing remediation time. Zinc, total nitrogen, total organic carbon, and electrical conductivity contents were statistically significantly different among samples throughout the bioremediation period (p ˂ 0.05). The ability of isolates to utilise hydrocarbons was highest for Pseudomonas and Bacillus species and lowest for Klebsiella and Serratia species. After a germination period of 12 days, a germination test showed that the bioattenuated polluted soil improved germination of bean seeds. Bioattenuation methods should be used and improved as a means of remediating petroleum-polluted sites because they are cost-effective and environmentally friendly.